Extraction of betulin — natural triterpenoid from Kirgyz birch Betula kirghisorum, an endemic plant of the Republic of Kazakhstan - Kasenov, R.Z.; Demets, O.V.; Kartbayeva, G.T.; Zhumadilov, S.S.; Alieva, M.R.; Zhumabekova, A.U.; Yergesh, A.A.; Bakibayev, A.A. (Fundamental and Experimental Biology, 2019)
On the territory of the Republic of Kazakhstan there are 15 species of birch trees, including 4 endemic spe-cies. This plant is a low tree with a reddish bark and a loose crown. On the territory of the Kent forestry of the Karkaraly State National Natural Park, a Kyrgyz birch bark was collected. Birch bark was crushed and dried to constant weight. From birch bark of the Kyrgyz with extraction method followed by recrystallization from isopropyl alcohol was isolated betulin. The melting point of the isolated substance was 243 ºC. Betulin was identified by thin layer chromatography and compared with a standard sample. The substance was analyzed by infrared spectroscopy methods in KBr tablets and high performance liquid chromatography (HPLC). In the Fourier spectrometer FSM-1201, the characteristic frequencies of the absorption bands were used to deter-mine the presence of various groups of atoms and bonds characteristic of betulin in the molecule. HPLC was used to study a sample using a Shimadzu LC-20 Prominence liquid chromatograph. Selected conditions for the qualitative and quantitative determination of betulin